"Dark hole" cure in Ba4.2Nd9.2Ti18O54 microwave dielectric ceramics. Issue 9 (July 2016) - Huang, Baoyu; Yan, Zhang; Lu, Xiaochi; Wang, Lixi; Fu, Zhenxiao; Zhang, Qitu
Abstract: Large size Ba4.2 Nd9.2 Ti18 O54 (BNT) ceramics doped with MnCO3, CuO and CoO were prepared by the conventional solid-state method. Only a single BaNd2 Ti4 O12 phase was formed in all samples. No second phase was found in the XRD patterns. The bulk density increases slightly because of the dopants. The SEM results showed that the grain size of Mn 2+ and Cu 2+ -doped BNT ceramics became larger with the increasing amount of dopants. The permittivity of all samples stays the same. However, the Q × f value of BNT ceramics increases by doping, especially with Mn 2+ ions. The conductivity of BNT ceramic doped with Mn 2+ (0.5 mol‰) under high temperature is lower than that without doping. There are fewer defects in Mn 2+ -doped BNT ceramics. The XPS results indicated that Ti reduction was suppressed in BNT ceramics doped with 0.5 mol‰ Mn 2+ . BNT ceramics doped with 0.5 mol‰ Mn 2+ ions sintered at 1320 °C for 2 h exhibited good microwave dielectric properties, with ε r =88.67, Q × f =7408 GHz and τ f = 82.98 ppm/°C.